INTERGATION OF INNOVATIVE PEDOGOGICAL TECHNOLOGIES IN THE PROCESS OF TEACHING NATURAL SCIENCES - Yulchieva , Zulfiya (Educational Research in Universal Sciences, 2023)
This article provides information on the effectiveness of the use of innovative educational technologies in the organization of natural science classes.